Pemberdayaan Ekonomi Masyarakat Melalui Penyuluhan tentang Peran Unit Pengumpul Zakat (UPZ) Desa Margaharja, Kecamatan Sukadana, Ciamis-Jawa Barat - Husni, Husni; Zuhri, M Syaifudin; Septian, Muhammad Yusuf; Nabhan, Arief; Nurhidayat, Deden; Tajurrahman, Aulia Azhari Tajurrahman (Khidmat, 2023)
This article presents a comprehensive account of the community service endeavors undertaken by both lectures and students. The objective of this community activity is to enhance the local economy by providing education about the functions of the Zakat Collection Unit (UPZ) in Margaharja Village, Sukadana District, Ciamis-West Java. The strategy employed for empowerment is the Islamic religious counseling approach. Empowerment strategies employed include lectures, interviews, dialogue, discussions, and practical exercises. The implementation of Islamic religious counseling to optimize the Margaharja Village Zakat Collection Unit (UPZ) has effectively enhanced the community's knowledge, understanding, insight, and awareness regarding the significance of zakat, infaq, and sadaqah for community development. The community's acceptance and understanding of the Margaharja Village UPZ's message on communal empowerment is facilitated by Islamic religious educators.